21st Century Maritime Silk Road: A Peaceful Way Forward - Zheng, Chongwei (Springer Oceanography,, 2018)
This book focuses on understanding the characteristics of the marine environment; overall characteristic of the marine resources (especially the marine new energy) and their current utilization; important routes, channels, and ports; and the Maritime Silk Road from the perspective of international law. It also discusses the significance and opportunities of the Maritime Silk Road initiative, analyzes the challenges involved in the construction of the Maritime Silk Road and provides corresponding countermeasures. Based on the above research, this book also proposes to construct a comprehensive application platform for the Maritime Silk Road that will be a practical tool for decision-making. This book is one of the series publications on the 21st century Maritime Silk Road (shortened as "Maritime Silk Road"). This series publications cover the characteristics of the marine environment and marine new energy, remote islands and reefs construction, climate change, early warning of wave disasters, legal escort, marine environment and energy big data construction, etc. contributing to the safe and efficient construction of the Maritime Silk Road. It aims to improve our knowledge of the ocean, thus to improve the capacity for marine construction, enhance the viability of remote islands and reefs, ease the energy crisis and protect the ecological environment, improve the quality of life of residents along the Maritime Silk Road, and protect the rights, interests of the countries and regions participating in the construction of the Maritime Silk Road. It will be a valuable reference for decision-makers, researchers, and marine engineers working in the related fields.